The use of expressive arts in making sense of traumatic experiences - Parr, Rachel Ann (2015)
Traumatic experiences brought about by natural disasters may find
survivors in a psychological state where rational and verbal modalities
are not always readily accessible. Play and Mindfulness-Based
Expressive Arts Therapy with Cognitive Reframing (PMBEAT) was
used to look into the experiences of 39 survivors of Typhoon Yolanda
through their individual and collective narratives. The resulting themes
of fear, anxiety, grief, isolation, guilt, and responsibility were generated
through the individual stories of the survivors shared in groupings
based on their developmental stages. The collective themes of unity
and transcendence were gleaned from the visual and verbal output
expressed in the family collage activity. The theme “A New Beginning”
was agreed upon by the entire group after reflecting on what represented
them as a whole. The interpretations and themes used in the study
were checked for reliability and accuracy using a modified “inter-rater
clinical judgment and discussion consensus” model.
Keywords: Super Typhoon Yolanda, 2013; Families and psychology